The Sarkisov program for Mori fibred Calabi-Yau pairs - Corti,A; Kaloghiros,A (Algebraic Geometry, 2016)
We prove a version of the Sarkisov program for volume preserving birational maps of Mori fibred Calabi–Yau pairs valid in all dimensions. Our theorem generalises the theorem of Usnich and Blanc on factorisations of birational maps of (C×)2 that preserve the volume form dx x ∧ dy y.